PENGEMBANGAN MEDIA POP-CULTURE ZONE DIGITAL BERBASIS STUDENT TEAMS ACHIEVEMENT DIVISION MODELS UPAYA PENINGKATAN MEMBACA PEMAHAMAN MAJAS SISWA KELAS V - Ahsanu Nadia, Isna; Dewi Purwati, Panca (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension skills are very important for the success of elementary school students, so they often become a challenge that can cause learning difficulties. The purpose of this study was to develop, test the feasibility, and test the effectiveness of a digital pop-culture zone media based on student teams achievement division models (STAD) to improve the reading comprehension of fifth-grade students. This study used the Research and Development (R&D) method by Borg and Gall in Sugiyono's book, which was modified into eight stages, including potential and problems; data collection; product design; design validation; design revision; preliminary testing; product revision; and usage testing. The digital pop-culture zone media consists of several components, namely the front cover, table of contents, instructions for use, foreword, learning outcomes and objectives, material, author profiles, and back cover. The digital pop-culture zone can be accessed offline using PowerPoint. The results of the media expert assessment were 91.67% and the material expert assessment was 95%, both of which were considered very feasible. The results of the teacher response were 92.85% and the student response was 96%, both of which were considered very feasible. The media effectiveness test using the T-test obtained a significant value of 0.000. The N-Gain calculation resulted in a value of 0.6454, which is considered moderate. Therefore, the digital pop-culture zone media based on STAD model is declared highly feasible and effective for improving reading comprehension.